Role of hyaluronic acid intrauterine injection in the prevention of Asherman's syndrome in women undergoing uterine septum resection: An RCT - Tafti, Seiede Zahra Ghanadzadeh (Int J Reprod Biomed, 2021)
BACKGROUND: Adhesion due to intrauterine surgery such as septal resection associated with damaged endometrium can increase the risk of Asherman's syndrome. The main goal of treatment in this syndrome is to repair the damaged endometrium for creating a physiological pregnancy. OBJECTIVE: To investigate the effect of intrauterine injection of hyaluronic acid on the prevention of Asherman's syndrome in women undergoing uterine septum resection. MATERIALS AND METHODS: In this double-blind randomized clinical trial, 65 women undergoing the uterine septum resection were divided into two groups; the case group (n = 34) and the control group (n = 31). Immediately after the septal resection with a resectoscope, 1cc of hyaluronic acid gel in the case group and 1cc normal saline solution as a placebo in the control group was injected into the uterine cavity. After two months, existence of intrauterine adhesions in the both groups was examined by the hysteroscope and assessment of menstrual patterns, according to the American Society for Reproductive Medicine criteria. RESULTS: Our results showed that after intervention, the incidence of Asherman's syndrome in the control group was higher than the case group (p = 0.012). In the case group, only four women had poor adhesion (Asherman's syndrome) at the end of the study, while the rest of them were free of any adhesions in the uterine cavity. In the control group, however, only 19 were free of intrauterine adhesions and 12 had mild symptoms. CONCLUSION: The results of the study exhibited the hyaluronic acid capacity to reduce the risk of Asherman's syndrome in women with endometrial damage following a septal resection surgery.